Stochastic analysis, stochastic systems, and applications to finance - Tsoi, Allanus Hak-Man, 1955-; Nualart, David, 1951-; Yin, George, 1954- (World Scientific, 2011)
This book introduces some advanced topics in probability theories - both pure and applied - is divided into two parts. The first part deals with the analysis of stochastic dynamical systems, in terms of Gaussian processes, white noise theory, and diffusion processes. The second part of the book discusses some up-to-date applications of optimization theories, martingale measure theories, reliability theories, stochastic filtering theories and stochastic algorithms towards mathematical finance issues such as option pricing and hedging, bond market analysis, volatility studies and asset trading modeling.